Pengaruh Suplementasi Betain terhadap Beberapa Parameter Lipida dan Protein Darah pada Puyuh - Aditya D Shenatmoko; Aris Kurniawan; C V Gebby; Adi Ratriyanto; Rysca Indreswari; Ratih Dewanti (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2013)
The objective of this research was to see the influence of betaine supplementation on some of blood lipid and protein parameters in laying quails. The research used four treatments based on completely randomized design. Each treatment was replicated five times with seventeen quails each.The treatments used 340 quails aged 4 weeks with average weigh 98.31±8.67 grams. The supplementation levels of betaine were 0 (control); 0.07; 0.14 and 0.21%. Twenty quails aged 14 weeks were taken from each replicate to determine blood lipid and protein. Data were analyzed by analysis of variance and if there was an effect of treatment, then it was analyzed by Duncan’s Multiple Range Test. The result showed that betaine supplementation at level 0.14% resulted higher level of low density lipoprotein compared with the other treatments. It could be concluded that betaine supplementation at 0.14% resulted higher concentration of low density lipoprotein than control.Key words: quail, betaine, blood lipid, blood protein